ANALISIS PENGUNGKAPAN EMISI GAS RUMAH KACA - Prafitri, Anistia; Zulaikha, Zulaikha (JURNAL AKUNTANSI DAN AUDITING, 2016)
This study aimes to examine the effect of environmental management system, company's environmental performance, company size, industry type, return on asset and leverage on the greenhouse gas emissions disclosures. The population are the agriculture, energy, transportation, base and chemical companies listed on the Stock Exchange in the year 2014-2015. Total samples used are 298 companies. Logistic regression is used to test the hypothesis. The results indicate that there is a positive and significant effect of the environmental management system, the company's environmental performance, company size, industry type, and leverage on the disclosures of greenhouse gas emissions, but return on asset don’t have effect on them